Effectiveness of Indian Jujube (Ziziphus mauritiana) Leaf Extract Using Ethanol Solvent Against Fall Armyworm (Spodoptera frugiperda) Under Laboratory Conditions - Rusli Rustam; Putri Indri Daviani; Pajri Ananta Yudha (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Maize (Zea mays L.) ranks among the major cereal crops globally, after rice and wheat. In Riau Province, a significant decline in maize yield has been observed, mainly due to infestation by fall armyworm (Spodoptera frugiperda J.E. Smith). Control of this pest is essential to prevent its population from exceeding economic thresholds. However, the predominant use of synthetic insecticides has led to undesirable consequences, including the development of resistance, pest resurgence, and secondary pest proliferation. As a sustainable alternative, botanical pesticides derived from plant-based compounds are gaining interest. This study investigated the insecticidal potential of Indian jujube (Ziziphus mauritiana Lamk) leaf extract prepared with 70% ethanol. This plant is known to contain various bioactive secondary metabolites, including alkaloids, saponins, and flavonoids. The experiment was conducted using a Completely Randomized Design with six extract concentrations (0, 0.2, 0.4, 0.6, 0.8, and 1.0%) and four replications, resulting in a total of 24 experimental units. The results showed that a 1% extract concentration produced the highest efficacy, resulting in 82.50% total larval mortality, with initial mortality observed at 7.25 h post-application. The LT₅₀ value was recorded at 52 h, while the LC₅₀ and LC₉₅ were estimated at 0.74 and 1.62%, respectively. These findings suggest that Indian jujube leaf extract has the potential to serve as an environmentally friendly biopesticide for controlling S. frugiperda under controlled conditions.